React front to back - Traversy, Brad (Packt Publishing, 2019)
"In this course, you will learn to master React 16.3+ concepts including the new Context API as well as Redux. We target certain concepts while progressively building real applications. Whether you have never touched React or have been working with it for a while and want to learn more and build some cool stuff, this course is for you. The final project will be a React/Redux client management panel which uses Firebase for authentication and Firestore to store data."--Resource description page